The Effectiveness of Indicators of Financial Discipline in Strengthening the Exchange Rate, with a Special Reference to Iraq - Fenjan, Karrar Mahdi; Salman, Muhammad Saleh (Journal of Economics and Administrative Sciences, 2021)
Controlling public expenditures is one of the main objectives of the public budget. The public budget often suffers from a deficit, whether in developed or developing countries, because expenditures are usually greater than the revenues generated. This requires the existence of financial rules that are adhered to by the government, which in turn leads to discipline. Fiscal policy leads to a reduction in the obligations incumbent on the government. Adhering to the financial rules would correct the course of fiscal policy in Iraq, with the need to direct oil revenues in the years of financial abundance when global oil prices rise to sovereign funds similar to other rentier countries, which contributes to maintaining the stability of the exchange rate and reducing dependence on The Central Bank. It performs monetary sterilization operations to sterilize the negative effects resulting from the lack of fiscal policy discipline, which negatively affects the foreign currency reserves and depletes them. The main conclusion reached by the research is that there is a state of financial indiscipline that has negatively affected the Iraqi dinar exchange rate, and that the attempts of the Central Bank of Iraq have partially worked to reduce the negative effects of the expansionary financial policy, and the main recommendation of the research was to work to achieve more discipline in fiscal policy in order to reduce the state of economic instability and mitigate the monetary sterilization policy by The Central Bank and the accompanying depletion of hard currency